Design and development of heat exchanger based on open cell metal foam / Ananthasayanam Subramani Sharath - Ananthasayanam Subramani , Sharath (2019)
The fluid flowing through pipes or ducts is commonly used in heating and were the liquids or the gas. The fluid in this type of flow is usually forced by a blower to bring about the preferred heat transfer. The equipment’s that ease this process are the Heat Exchangers. The Copper metal foams with 60 PPI (Pores Per Inch) was chosen to develop the Heat Exchanger. The primary objective of the research in developing a compact metal foam heat exchanger in different configuration was achieved. Firstly, the Design 1 was a type of Heat Exchanger that the copper metal foams and the aluminum fins are arranged consecutively and closely packed. Secondly, the Design 2 was a type of Heat Exchanger that the pair of aluminum fins and foams were arranged with air gap of 5mm in between. The Novelty of this research lies with the Different design and the configuration of the metal foam arranged in the housing with the maximum pore density of 60 PPI. The Experimental Investigation of both the designs were studied separately based on the Velocity Profile, Pressure Drop, Heat transfer coefficient and the Temperature Difference. The effects of each mentioned above were studied and analyzed by varying velocity from 0.8m/s to 2.3m/s. The experiments were conducted under steady state conditions of maintaining the constant room temperature and the constant heat flux of 50˚C. The Heat transfer characteristics of each localized points from H11 to H51 and H12 to H52 in the heat exchanger for both the design1 and 2 were studied thoroughly. The average Nusselt number for both designs was evaluated based on the average heat transfer coefficient and has been compared with the analytical equation and the previous study.